PENTINGNYA PENGETAHUAN USIA DEWASA MENURUT HUKUM BAGI MAHASISWA DI PERGURUAN TINGGI - Delila Kania; Deni Zein Tarsidi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
Abstract This study aims to reveal how the understanding of adult age according to applicable law in Indonesia is for students of the Pancasila and Citizenship Education Study Program (PPKn) semester 1 (one) for the 2021-2022 academic year. The students in the subject of this research are aspiring teachers. Citizenship Education has the goal of making good citizens. The research method used is a case study approach to determine the extent of knowledge and understanding of legal adulthood in these students. Observations and interviews with semester 1 (one) students are to ensure the results of case study research. The implications of this legal age of adult knowledge will have an impact on understanding their rights and obligations as citizens. Students as legal subjects should know and understand the age of adulthood according to applicable law in Indonesia. This knowledge is very useful for students to protect their rights and interests in the life of the nation and state.